La higiene del ganado y la fasciolosis bovina, Medellín y Rionegro, 1914-1970 (2006)
ABSTRACT: In the approach of bovine fasciolosis biomedical studies, historical research has become necessary. Here we deal with the historical aspects in Medellín and Rionegro during most of XX century. The importance and dynamism of cattle activity in Antioquia during XX century partially explains private and official interests in improving this sector of economy through disease prevention. Since 1914, a local sanitary policy emerges, concerning control for food coming from animal brood. While milk production increases, the requirement of veterinary control and teaching appears in Colombia. Although bovine fasciolosis reports can be followed since the first decades of XX century, it does not appear as a main concern in biomedical and sanitary reports from Medellín and Rionegro. Studies regarding this disease, published in several national newspapers and journals from the first middle of XX century, circulated among specialists and did not have an influence in cattle in Colombia. Moreover, an evaluation of documents belonging to the last decades of XX century suggests that, despite the high disease incidence, fasciolosis research has not had an impact in the development of prevention and control programs.